36th Annual David W. Smith Workshop on Malformations and Morphogenesis: Abstracts of the 2015 annual meeting. Issue 7 (27th April 2016) - Gripp, Karen W.; Adam, Margaret P.; Hudgins, Louanne; Carey, John C.
Abstract : The 36th Annual David W Smith Workshop on Malformations and Morphogenesis was held on August 14–19, 2015 at the Harbourtowne Conference Center in St. Michaels Maryland. The Workshop, which honors the legacy of David W Smith, brought together over 120 clinicians and researchers interested in congenital malformations and their underlying mechanisms of morphogenesis. As is the tradition of the meeting, the Workshop highlighted five themes besides mechanisms of morphogenesis: Rasopathies, Eye Malformations, Therapeutics, Prenatal Diagnosis, and Disorders of Sex Development. This Conference Report includes the abstracts presented at the 2015 Workshop. © 2016 Wiley Periodicals, Inc.